THE EFFECT OF THE EXISTENCE OF PANGSAN TOURISM VILLAGE ON CHANGES IN LAND USE, ECONOMIC, AND SOCIAL COMMUNITIES - Adi Husnaini (International Journal of Sustainable Competitiveness on Tourism, 2023)
Tourism is one of the main sectors in Indonesia to improve the economy. The strategy in developing the economy, especially in rural areas, is to develop tourism villages. As one of the sectors that occupy space development, directly or indirectly, will affect changes in economic conditions, social and physical geography. Pangsan Village is located in Petang District, Badung Regency. The development of this tourism village is certainly an impact on the physical and non- physical conditions in the village. Based on this statement, this study was conducted to assess the influence of Pangsan Tourism Village existence toward land-use changing, economic and social. The method used in this study is Descriptive quantitative method. These results indicate that the presence of Pangsan Tourism Village affects changes in land use where forests and rice fields are used as tourist attractions to support tourism activities. The existence of the tourism village also has an effect on the economy, especially the expansion of job opportunities and increased revenues. The developments of a tourism village with many tourists who come also affect social conditions that are reflected in the patterns of behavior and attitude of people skills. As for the distribution of increased community skills gained from training for manage the tourism village. The results of the research are expected to be a guideline for stakeholders to develop Pangsan Tourism Village Keywords: Tourism Village, Land-Use Change, Economic, Social